2012
DOI: 10.1039/c2cc34163h
|View full text |Cite
|
Sign up to set email alerts
|

Probing excited state electronic communications across diethynyl-[2.2]paracyclophane-containing conjugated organometallic polymers

Abstract: The triplet k(ET) for three organometallic polymers built upon the diethynyl[2.2]paracyclophane was studied to show good excited state electronic communication across the materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Very recently, Knorr, Harvey, and co-workers reported the triplet k ET value for energy transfer through [2.2]paracyclophane in a platinum-containing through-space conjugated polymer. The k ET value by the Dexter mechanism was estimated to be approximately on the order of 10 5 s À1 , 12 which is much smaller than the k ET value for transfer by the Fçrster mechanism discussed above. [22] Thus, it is concluded that in our system, the Fçrster-type energy transfer is dominant because of the fixation of the donor and acceptor in close proximity (small R value), the good spectral overlap between the PL spectrum of the donor and the absorption spectrum of the acceptor (large J value), and the favorable orientation of the donor and acceptor (large k 2 value).…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…Very recently, Knorr, Harvey, and co-workers reported the triplet k ET value for energy transfer through [2.2]paracyclophane in a platinum-containing through-space conjugated polymer. The k ET value by the Dexter mechanism was estimated to be approximately on the order of 10 5 s À1 , 12 which is much smaller than the k ET value for transfer by the Fçrster mechanism discussed above. [22] Thus, it is concluded that in our system, the Fçrster-type energy transfer is dominant because of the fixation of the donor and acceptor in close proximity (small R value), the good spectral overlap between the PL spectrum of the donor and the absorption spectrum of the acceptor (large J value), and the favorable orientation of the donor and acceptor (large k 2 value).…”
mentioning
confidence: 75%
“…However, conjugated polymers containing cyclophane skeletons in the conjugated polymer main chain have been ignored until recently. [5,[9][10][11][12] We have incorporated [2.2]paracyclophane into conjugated polymer backbones and evaluated the various characteristics of cyclophane-based through-space conjugation. To obtain a better understanding of these through-space conjugated polymers, herein, we prepared a through-space conjugated dimer, in which two pelectron systems are stacked in a single molecule.…”
mentioning
confidence: 99%
“…Absorption (abs), excitation (grey), and emission spectra of HC CÀPCPÀC CH (55; in 2MeTHF, 77 K; up) (Àtrans-Pt(PBu 3 ) 2 ÀC CÀPCPÀC CÀ) n (56; in 2MeTHF, 77 K; middle) and (ÀPt 2 (dppm) 2 ÀC CÀPCPÀC CÀ) n (57; solid state, 298 K; bottom). [72] Figure 25.…”
Section: [22]paracyclophane-containing Polymersmentioning
confidence: 96%
“…Stuctures of the bis(ethynyl)[2.2]paracyclophane-containing polymers. [72] Co 2 (CO) 6 (m-h 2 -PCPÀC CH) [69] (51) for which the coloured Co 2 (CO) 6 cluster unit exhibits non-luminescent lower energy S 1 and T 1 excited states ( Figure 23). These investigations are clearly important in order to address the behaviour in conjugated organometallic polymers built upon bis(ethynyl)ÀPCP bridges.…”
Section: [22]paracyclophane-containing Polymersmentioning
confidence: 99%
“…The theoretical calculations described above were carried out on the assumption that Förster‐type7 energy transfer occurred, disregarding the Dexter‐type11 energy transfer. Recently, Knorr and Harvey reported the triplet‐state energy transfer, which is performed by the Dexter mechanism, using platinum‐containing through‐space conjugated copolymers 12. The k ET values were calculated to be on the order of 10 4 –10 5 s −1 .…”
Section: Resultsmentioning
confidence: 99%